KESULITAN METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA PADA MATERI PELUANG DITINJAU DARI TIPE KEPRIBADIAN TIPOLOGI HIPPOCRATES â GALENUS KELAS XI MIA 1 SMA NEGERI I SOE - Bulu, Vera Rosalina; Budiyono, Budiyono; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of research was to describe difficulty, cause, and solution to the difficulties the 11th MIA 1 Grades of SMA Negeri I Soe faced in using their metacognitive of ability to solve mathematics problem in probability material using melancholic, sanguinic, phlegmatic and choleric personality types. This study was an exploratory qualitative research. The procedure used of selecting subject is snowball sampling, so that 12 subjects were obtained whose data could be analyzed. The data collection was conducted using think aloud method. The data validation was carried out using time triangulation. Techniques of analyzing data used were: (1) classifying data into 4 categories: (a) understanding problem, (b) thinking about plan, (c) implementing the plan, (d) rechecking the answer, (2) presenting the data in narrative text and (3) drawing a conclusion about difficulty, cause, and solution to metacognitive difficulty in each category. The results of research showed that the metacognitive difficulties in solving problem of probability material for melancholic and choleric students were as follows. (a) The students difficulty realized strategic deliberation and the advantage of strategy used, (b) Students experience metacognitive difficulty in realizing the strategic change when they were wrong, (c) Difficulty in realizing the evaluation on confusion, (d) Difficulty in realizing when a strategy is used, (e) Difficulty in realizing the different strategies, (f) Difficulty of other strategy in problem solving, (g) Difficulty in realizing their work product evaluation, and (h) Difficulty in realizing the consideration of all options in solving problem. The difficulty of sanguinic and phlegmatic students were as follows. (a)Â  Difficultly realized strategic deliberation and the advantage of strategy used, (b) Difficulty in realizing the advantage of strategy used (c) Difficulty realizing when a strategy was used (d) Difficulty in realizing when a strategy was used (d) Difficulty in realizing the reason of using different strategies inÂ  various situation (e) Difficulty in realizing other strategy in solving problem and (f) Difficulty in realizing the deliberation of all options in solving problem.Keywords: Metacognitive Difficulty, Problem Solving, Hippocrates-Galenus Personality Type.Â